Metode Takroran dalam Pembelajaran Kitab Amtsilati di Pondok Pesantren Hidayatul Mubtadi’in Gurah Kediri Perspektif Teori Belajar Kognitif - Auliya Akbar Rahmatullah (Pendidikan Bahasa Arab Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This study aims to determine the application of takroran method in Amtsilati book with the perspective of cognitive learning theory. This research is a field research using a descriptive approach. Data were collected through observation instruments, interviews, questionnaires, and documentation. The collected data is then analyzed by data reduction to then present the data and give conclusions. The results of this study are: 1) The takroran method is the application of the knowledge of Nahwu and Shorof to be able to read the yellow book (kitab kuning) properly and correctly. 2) In focusing its students on understanding the Amtsilati method, the Hidayatul Mubtadi'in Islamic boarding school prepares skilled teachers to explain the book easily and pleasantly with supporting cottage facilities. 3) Cognitive learning theory is the closest learning theory in the implementation of the Takroran method at Hidayatul Mubtadi'in Amtsilati Gurah Kediri boarding school. 4) The Takroran method covers aspects of cognitive learning theory in the form of aspects of knowledge, understanding, application, analysis, synthesis, and assessment.